A.C.A … All Coppers Are … an analysis of police legitimacy in Spain - Vazquez, David; Aizpurua, Eva; Leon, Carmen M. (Policing and Society, 2023)
In Spain, knowledge about public attitudes towards the police is limited compared to other countries. This study contributes to fill gaps in the literature by examining a wide range of correlates of police legitimacy. Using data from the Spanish sample (N = 1,885) of the European Social Survey (ESS) Round 5, we estimate multivariate regression models with two measures of police legitimacy as outcome variables: moral alignment (α =.81) and duty to obey the police (α =.86). Correlates encompass a range of attitudinal measures, including those related to police activity, the sociopolitical and institutional context, and personal characteristics of the respondents. The results show that, in Spain, as in other countries, police legitimacy is primarily influenced by perceptions of procedural fairness and effectiveness. In addition, the study found that variables such as political orientation and attitudes towards the sociopolitical context are also relevant. These findings suggest that people’s views of the police are linked to broader social and political factors, beyond their interactions with the police.
Keywords: legal authority; legitimacy; police; procedural justice; public opinion; Scopus; JCR